2000
DOI: 10.1007/s004310051297
|View full text |Cite
|
Sign up to set email alerts
|

Malignant osteopetrosis obscured by maternal vitamin D deficiency in a neonate

Abstract: Osteopetrosis is an important differential diagnosis of neonatal rickets and is not excluded by low vitamin D levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…However, Popp et al 8 reported a patient with osteopetrorickets complicated by vitamin D deficiency in the neonatal period. First, the patient was diagnosed with neonatal rickets due to maternal vitamin D deficiency and after the appropriate treatment of rickets, the patient developed features of osteopetrosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, Popp et al 8 reported a patient with osteopetrorickets complicated by vitamin D deficiency in the neonatal period. First, the patient was diagnosed with neonatal rickets due to maternal vitamin D deficiency and after the appropriate treatment of rickets, the patient developed features of osteopetrosis.…”
Section: Discussionmentioning
confidence: 97%
“…In these cases, there is a risk of developing hypocalcemia, with attendant tetany and seizure. In osteopetrosis, there is excess calcium reserve and hypophosphatemia, but when the calcium x phosphorus product (chronically less than 30 mg 2 /dl 2 ) is insufficient to mineralize newly formed bone matrix, development of rickets is probable 4,7,8 . Calcium/phosphorus product in our patient was 20 mg 2 /dl 2 at diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Popp et al (19) have suggested that low levels of vitamin D can obscure osteopetrosis signs. The absence of CD68+ osteoclasts in the trephine biopsy suggests that TRAF6 is essential for osteoclast differentiation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the TRAF6 protein in our patients led to a proclivity of the OP phenotype for the pelvis and legs, at least temporarily sparing the upper part of the body, a phenomenon for which we do not have an explanation. Popp et al have suggested that low levels of vitamin D can obscure osteopetrosis signs. Our patients have had low levels of vitamin D at first evaluation, and high‐dose supplementation of Vitamin D precluded assessment of its effect on the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of sclerotic bone results in reduced marrow space and narrowed 4 . This balance can lead to a reduction in bone mass, as seen in osteoporosis, or to abnormal accumulation of bone tissue, as observed in osteopetrosis 1 .…”
Section: Introductionmentioning
confidence: 99%